Impact of Two Different High-power Pain Threshold Static Ultrasound Techniques on Myofascial Trigger Points: A Pilot Study - Anand Kumar Singh; Kamran Ali (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Myofascial Pain Syndrome (MPS) is a challenging musculoskeletal condition with a prevalence of upto 30% in certain populations seeking medical care. It is characterised by Trigger Points (TrPs) in muscle fibres, leading to spontaneous pain, referred pain, muscle tension, and restricted Range Of Motion (ROM). The integrated TrP hypothesis proposes that an energy crisis triggers TrPs through calcium release, prolonged muscle activity, and localised ischaemia. Vasoactive substances sensitise nociceptors and perpetuate the cycle. High-power Pain Threshold Ultrasound (HPPTUS-9), a novel Ultrasound (US) therapy, shows promise in reducing pain from active TrPs. The present study investigates the effects of HPPTUS-9 on Pressure Pain Threshold (PPT), subjective pain intensity, lateral flexion ROM, and disability in MPS patients. Aim: To determine the impact of two different HPPTUS techniques on MTrPs. Materials and Methods: A randomised clinical trial was conducted using a two-way mixed analysis of variance at the Department of Physiotherapy, GD Goenka University in Gurugram, Haryana, India, over a four-month period from April 2023 to August 2023. A total of 16 individuals with TrPs in the upper trapezius muscle, comprising seven males and nine females, were included. They were equally divided into two groups: the HPPTUS-9 group 1 and the HPPTUS group 2. Both groups received treatments over a six-session period spanning two weeks. The primary outcome measure was the PPT, which evaluated the pain threshold of TrPs in the upper trapezius muscle. The secondary outcome measures included ROM, Neck Pain Disability Index (NPDI), and subjective pressure pain intensity. Statistical analysis was conducted using paired t-tests. Results: Between-group analysis revealed that participants who underwent nine applications of HPPTUS experienced a significantly greater increase in PPT (p=0.001) and ROM (p=0.001) compared to the other group at the end of the two-week intervention. Additionally, both groups demonstrated a significant decrease in pain (p=0.002) within their respective treatments. Notably, no adverse effects were reported in either group. Conclusion: The present study demonstrates that nine applications of HPPTUS led to significant improvements in PPT and ROM compared to the alternative treatment group. Both groups showed a notable reduction in pain during their respective interventions. Importantly, no adverse effects were reported in either group throughout the two-week study period. These findings suggest that HPPTUS has the potential to be an effective and safe treatment option for addressing pain and mobility issues.